ATIM-05. INTRATUMORAL DELIVERY OF MDNA55, AN INTERLEUKIN-4 RECEPTOR TARGETED IMMUNOTHERAPY, BY MRI-GUIDED CONVECTIVE DELIVERY FOR THE TREATMENT OF RECURRENT GLIOBLASTOMA. (5th November 2018) - Achrol, Achal; Bexon, Martin; Bankiewicz, Krystof; Brenner, Andrew J; Butowski, Nicholas; Kesari, Santosh; Merchant, Fahar; Merchant, Rosemina; Randazzo, Dina; Vogelbaum, Michael; Zabek, Miroslaw; Sampson, John
Abstract: While intratumoral delivery of immunotherapies allows for targeted distribution and minimal systemic toxicity, optimal spatial distribution of therapeutic agents remains a challenge. MR-guided convection-enhanced delivery of MDNA55, interleukin-4 cytokine fused to Pseudomonas exotoxin, is currently being explored in a Phase 2 open label study in up to 52 patients with recurrent glioblastoma. MDNA55 is coinfused with a Gadolinium-based contrast agent (GdDTPA) and delivered as a single infusion using implantable flexible catheters. MRI was employed to monitor initial infusion, allowing adjustment of catheter depth as needed. The bulk of the delivery was performed outside the MRI scanner while patients were awake. MRI confirmation of distribution was performed within 4 hours post-infusion. Here we report preliminary results of tumor distribution in 23 subjects. Total volume of MDNA55 (ranging from 12 mL to 66 mL) was initially administered to subjects (n=12) based on tumor size. This achieved a mean coverage of 75% (range 46 – 94%) with 17% showing volume of distribution > 100 mL. Review by the Safety Committee determined that improvements to drug distribution could be further enhanced by moving to a fixed volume of 60 mL administered via 4 catheters and allowing placement outside the peritumoral area if necessary. Treatment in the next 11 subjects showed that infusion volumes exceeding 40 mL and placement of catheters outside the enhancing tumor led to increased volumes of drug distribution (45% showed volume of distribution > 100 mL) but did not improve the target percentage coverage of the tumor (mean 60%, range 22 – 97%) and its immediate penumbra. Therefore, under the current protocol version, all subjects are receiving individualized volume of MDNA55 (according to tumor size), but not exceeding 40 mL. Further optimization is underway to ensure adequate coverage and improve drug distribution.